Syari’ah Appraisal On Mudharabah (Profit and Risk Sharing) Product In Islamic Banking And Financial Institutions In Indonesia (Prosiding Keislaman dan Sains, 2025)
This study is designed mainly to assess the Syari’ah compliance on mudharabah (profit and risk sharing) product offered by Islamic banking and financial institutions in Indonesia. This study employs the descriptive analysis based on syari’ah perspective. As a result, the study found that the product of mudharabah (profit and risk sharing) offered by Islamic banking and financial institutions were problem and not totally Islamic. The most reasonable arguments of the problem were derived from the operating system of Islamic banking and financial institutions which is parallel with the conventional counterparts that prohibited by Islam. The problem are as follows: (1) conflict in dual system of funding and financing based on the concept of real mudharabah and mudharabah musytarakah; (2) Islamic banking and financial institutions do not have real business; (3) Islamic banking and financial institutions are not able to bear losses; (4) Islamic banking and financial institutions customers are given profit sharing, whereas some of the cutomers’ funds have not yet been invested; (5) and profit sharing calculation method is convoluted or complicated. Therefore, to overcome the significant problem, it is necessary to reform the current operation of Islamic banking and financial system. Besides that, the optimalization of the Shari’ah supervision (al-raqabah syar’iyyah) aspect should be taken positively and seriously by the National Syari’ah Council of the Indonesian Ulama’ Council in order to prevent the Islamic banking and financial institutions from breaking the Syari’ah principles and values.
Keywords: Islamic Banking and Financial (IBF) institutions; Pure mudharabah (profit and risk sharing); mudharabah musytarakah (two tier mudharabah); syari’ah Islamiyah